Jatropha curcas oil as a bio-based rejuvenating agent for reclaimed asphalt pavement mixtures - Abdullahi Ahmad, Kabiru (2019)
Recycled asphalt pavement (RAP) is the most effective way to reduce the use of fresh asphalt binder and to consider its application at a higher percentage for the preparation of Hot Mix Asphalt (HMA). Use of RAP in HMA helps to lower the consumption of virgin aggregates and binder, consequently the construction cost and conservation of energy. This research investigates the performance of Jatropha curcas oil (JCO) as a bio-based rejuvenating agent for reclaimed asphalt binders and mixtures. The optimum JCO content was determined through asphalt binder test. A total of 4% JCO by mass of asphalt binder (40% RAP + 60% virgin binder) was incorporated into the binder and mixtures. The effects of JCO on asphalt binder and mixture were investigated via physical properties test, bleeding test, diffusion test, rheological properties, chemical properties and mixtures performance test, respectively. The test results show that the incorporation of JCO with virgin binder decreased the viscosity and improved the visco-elastic properties of the rejuvenated binder. Viscosity reduction was also observed when JCO incorporated with reclaimed asphalt binder. Hence, this indicates the potential to reduce the production temperature of the RAP mixture. From the rheological master curves, the addition of JCO decreased the complex modulus values compared to the virgin binder sample. Atomic force microscopy (AFM) and Fourier Transform infrared (FTIR) test results showed the ability of JCO to reduce the effects of aging. The performance of recycled asphalt mixtures was improved in terms of workability, while reducing the fuel requirement and GHG emissions gas released during the production of the mixtures. Moreover, the addition of JCO improves the adhesion between the recycled binder and aggregate, therefore, providing more resistance to moisture damage.